2021
DOI: 10.3390/en14061516
|View full text |Cite
|
Sign up to set email alerts
|

Sediment and Cavitation Erosion in Francis Turbines—Review of Latest Experimental and Numerical Techniques

Abstract: Sediment and cavitation erosion of the hydroelectric power turbine components are the fundamental problems in the rivers of Himalayas and Andes. In the present work, the latest research conducted in both the fields by various investigators and researchers are discussed and critically analyzed at different turbine components. Analysis shows that both types of erosion depends on flow characteristics, surface, and erodent material properties. Design optimization tools, coalesced effect (CE) of sediment and cavita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 45 publications
0
6
1
Order By: Relevance
“…Quartz is typically the predominant mineral found in most rivers, while in this study, plagioclase minerals composed the greatest part of the sediments found in Pastaza River. Nevertheless, the hardness values did not seem to differ significantly from other studies [10][11][12]14]. Comparing the shape of the sediments with the sample chart, the sphericity and roundness were found to be S = 0.7 and R = 0.3, respectively.…”
Section: Mineral Compositioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Quartz is typically the predominant mineral found in most rivers, while in this study, plagioclase minerals composed the greatest part of the sediments found in Pastaza River. Nevertheless, the hardness values did not seem to differ significantly from other studies [10][11][12]14]. Comparing the shape of the sediments with the sample chart, the sphericity and roundness were found to be S = 0.7 and R = 0.3, respectively.…”
Section: Mineral Compositioncontrasting
confidence: 52%
“…He proposed changing the opening of the guide vanes to improve turbine efficiency and reduce the erosion rate [13]. Moreover, Noon and Kim discussed and analyzed the latest experimental and numerical techniques to determine sediment and cavitation erosion on different turbine components using baseline data from the Tarbela Dam hydroelectric project in Pakistan [14]. However, all the aforementioned studies were performed in Asia, and no research on the topic has been performed on South America, where similar erosion issues are found.…”
Section: Introductionmentioning
confidence: 99%
“…There can be three types of side-wall clearance between guide vanes and runner i.e., guide vanes being above the level of the runner (clearance type 1), runner being above the level of the guide vanes (clearance type 2), and both the runner and the guide vanes being in the same level. In Francis turbine, operating in sediment-laden flow, erosion concentrations were observed in the region of the GV and the runner blade [11,12]. More importantly, sever erosion was observed in side-wall clearance region of Francis runner as shown in Figure 4.…”
Section: Introductionmentioning
confidence: 94%
“…This affects energy production and environmental protection since hydroelectric power is frequently used due to its commonality and significant contribution to total energy production [1]. The degradation of turbine blades caused by erosion processes such as cavitation and sediment erosion produces a challenge and an additional cost associated with energy production [2]. Cavitation is the process of the formation of vapor bubbles in low-pressure regions within a fluid, produced when the hydrostatic pressure acquires a value lower than the saturation vapor pressure [3].…”
Section: Introductionmentioning
confidence: 99%
“…Although cavitation or erosion studies often utilize both numerical and experimental methods, relying solely on numerical techniques may seem efficient, yet it disregards crucial factors. Numerical methods, while time-and resource-saving, encounter challenges stemming from various parameters [2,6,7]. These parameters interplay, where temperature fluctuations within the liquid flow impact pressure fluctuation amplitudes and wave velocities [8,9].…”
Section: Introductionmentioning
confidence: 99%